PENDIDIKAN KESEHATAN PENINGKATAN PENGETAHUAN TENTANG PENCEGAHAN PENYAKIT TIDAK MENULAR - Girsang, Vierto Irennius; Purba, Ivan Elisabeth; Harefa, Karnirius (Jurnal Abdimas Mutiara, 2022)
Non-Communicable Diseases (NCDs) are diseases that are not caused by an infectious process (not infectious) and cannot be transferred from one person to another. The risk factors for non-communicable diseases are influenced by the progress of the era of globalization which has changed the perspective of the world's population and gave birth to new habits that are not in accordance with a healthy lifestyle. The increase in the prevalence of non-communicable diseases is related to an unbalanced lifestyle and diet, including smoking, consumption of alcoholic beverages, physical activity, and less consumption of fruits and vegetables. The method applied in this community service activity is lectures and light discussions. The material will be presented in the form of power points by including several learning videos. The targets and objectives in this community service activity are the assisted citizens at the Class I Special Guidance Institute Medan. This community service activity was carried out in November 2021 at the Medan Class I Special Guidance Institute. The number of participants in this activity is 16 people. This community service activity lasted for 60 minutes by implementing health protocols. Each participant found it very useful to participate in this community service activity. Participants who attended this community service activity were very enthusiastic because this activity could increase their knowledge about non-communicable diseases and their prevention.